Generation of High-Quality Cylindrical Vector Beams from All-Few-Mode Fiber Laser - Pingping Xiao; Zhen Tang; Fei Wang; Yaqiong Lu; Zuxing Zhang (Photonics, 2024)
Transverse mode control of laser intracavity oscillation is crucial for generating high-purity cylindrical vector beams (CVBs). We utilized the mode conversion and mode selection properties of two-mode long-period fiber gratings (TM-LPFGs) and two-mode fiber Bragg gratings (TM-FBGs) to achieve intracavity hybrid-mode oscillations of LP01 and LP11 from an all-few-mode fiber laser. A mode-locked pulse output with a repetition rate of 12.46 MHz and a signal-to-noise ratio of 53 dB was achieved with a semiconductor saturable absorber mirror (SESAM) for mode-locking, at a wavelength of 1550.32 nm. The 30 dB spectrum bandwidth of the mode-locked pulse was 0.13 nm. Furthermore, a high-purity CVB containing radially polarized and azimuthally polarized LP11 modes was generated. The purity of the obtained CVB was greater than 99%. The high-purity CVB pulses have great potential for applications in optical tweezers, high-speed mode-division multiplexing communication, and more.